Urban Farming to Ensure Food Security and to Generate Cash Income During the Covid-19 Pandemic: A Case Study in Bausasran Urban Village Indonesia - Himmah Mahmudah; Subejo; Krishna Agung Santosa (LPPM Politeknik Aceh Selatan, 2024)
The Covid-19 pandemic proved to be a momentum for the Gemah Ripah Farmer Group (GRFG), even though with a small area of land, they were able to continue providing food through urban farming. They were able to inspire the growth of vegetable villages and received several awards for their contributions. This research aims to analyze the implementation of urban farming so that it can serve as food security and cash income during the Covid-19 pandemic. The research was conducted in Bausasran urban village, Danurejan sub-district, Yogyakarta province, Indonesia. The present study was conducted using a qualitative method with a case study approach, where data were collected through semi-structured interviews, observations, discussions, and documentation studies. The results show that the implementation of urban farming in the GRFG is effective as an alternative solution in providing and maintaining food availability during the pandemic, since vegetables and fruits are ready to be picked from the garden at any time. It reduces food expenditures and generates cash income for its members through the sale of processed urban agriculture products and educational tourism. This study provides an example of how innovative urban farming can help strengthen the economy of a community.